PENINGKATAN KETERAMPILAN MEMBACA SISWA MELALUI MEDIA FLASHCARD ABJAD SISWA KELAS II UPT SD NEGERI 107 INPRES KUNJUNG KABUPATEN TAKALAR - Hasnah; Abdul Rahman Rahim; Haslinda (STKIP Subang, 2026)
The main issue in this study is how to improve the reading skills of second-grade students at UPT SD Negeri 107 Inpres Kunjung, Takalar Regency, through the use of alphabet flashcards. This study aims to improve the reading skills of second-grade students at UPT SD Negeri 107 Inpres Kunjung, Takalar Regency, through the use of alphabet flashcards. This study is a classroom action research consisting of two cycles, with each cycle conducted over four meetings. The research procedure included planning, implementation of actions, observation, and reflection. The subjects in this study were 26 second grade students at UPT SD Negeri 107 Inpres Kunjung, Takalar Regency. The results showed that in cycle I, only 7 or 27% of the 26 students individually met the learning achievement criteria (KKTP) or were in the low category. Classically, the criteria were not met because the average score was 57.6%. Meanwhile, in cycle II, 23 out of 26 students, or 88%, met the KKTP, and classically, the average score obtained was 82.3%, which was in the very high category. Based on the above research results, it can be concluded that the Indonesian language learning outcomes of second-grade students at UPT SD Negeri 107 Inpres Kunjung, Takalar Regency, through the use of alphabet flashcards have improved. Keywords: Reading Skills, Alphabet Flashcards